2013
DOI: 10.1002/app.40167
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial electrospinning and release characteristics of cellulose acetate–gelatin blend encapsulating a model drug

Abstract: In order to minimize the degradation of encapsulated compounds in the harsh environment of release medium and to minimize bursting release, a model drug was encapsulated in a kernel of ultrafine cellulose acetate (CA) and gelatin (GL) blend fibers via coaxial electrospinning. The effects of the GL ratio on the properties of the shell solution were investigated, along with the core-to-shell ratio. Transmission electron microscopy images showed that core-shell coaxial fibers were fabricated successfully. Scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Addition of HW in the emulsions leads to a decrease on the conductivity. For instance, conductivity of UTHW (1.3 mS/m) is well below that of BLUT (3 mS/m), with the first being comparable to the data obtained by Kiatyongchai et al (2014). This is probably due to the complexes that are formed between WPI and EGCG and mentioned earlier.…”
Section: Fig 9 3 Proposed Mechanism Of the Emulsification In The Case That Catechin Is Added In Aqueous Phasesupporting
confidence: 80%
See 1 more Smart Citation
“…Addition of HW in the emulsions leads to a decrease on the conductivity. For instance, conductivity of UTHW (1.3 mS/m) is well below that of BLUT (3 mS/m), with the first being comparable to the data obtained by Kiatyongchai et al (2014). This is probably due to the complexes that are formed between WPI and EGCG and mentioned earlier.…”
Section: Fig 9 3 Proposed Mechanism Of the Emulsification In The Case That Catechin Is Added In Aqueous Phasesupporting
confidence: 80%
“…By this method, the components immiscibility problem is solved (Pérez-Masiá et al, 2014). Various studies have been shown the potential use of coaxial electrospraying mostly in pharma applications (Cao et al, 2014;Kiatyongchai et al, 2014).…”
Section:  Coaxial Electrosprayingmentioning
confidence: 99%
“…Most reports of tunable and sustained release from coaxial fibers describe the delivery of macromolecules (e.g., proteins and nucleic acids) [811] or hydrophobic small molecules [10,1214], where sustained release is aided by their large size, poor solubility or favorable partitioning into insoluble polymers. For hydrophilic small molecules that are often incompatible with hydrophobic polymers used for sustained release, low drug loading into the core of a coaxial fiber can facilitate slow drug release [1517,21]. Here, we show high drug loading (up to 39 wt% in core-shell fibers) of a hydrophilic small molecule drug and sustained release over at least 5 days in vitro by ensuring compatibility between maraviroc, EC, and PVP.…”
Section: Discussionmentioning
confidence: 68%
“…Consequently, quite a few studies focus on the preparation and drug release of electrospun fibers prepared from biopolymers and Amox, in order to use them as drug delivery systems. These studies include the optimization of the preparation process, the modification of properties, the control of drug release, and microbiological effects [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Valarezo et al [ 20 , 21 ], for example, prepared fibers from poly(lactic acid) (PLA)/polycaprolactone (PCL) blends containing Amox and could control the rate of drug release by adjusting the ratio of the two polymers.…”
Section: Introductionmentioning
confidence: 99%